When Does S(he) Plan to Retire? Antecedents of Retirement Age In Family Businesses - Diaz-Matajira, Luis; Sinn, Francisca; Sandoval-Arzaga, Fernando; Davis, James (European Journal of Family Business, 2023)
The family CEOs' intention to retire seems to be critical to trigger the succession process. For a more comprehensive understanding of the leadership succession in family businesses, it is important to study the antecedents of the family CEO's intended retirement age. Using a global database, we examine the incumbents' retirement age from their own perspective as the determinant of retirement timing. We apply the theory of planned behavior to explore factors affecting retirement age with a forward perspective, using the intended age of retirement as an antecedent for effective retirement age. Our results suggest that individual factors of the intended retirement age have stronger explanatory power in leader intended retirement age compared to the family business factors.